Protective effects of N-acetylcysteine on triamcinolone acetonide-induced lens damage in rats. (December 2014) - Tuzcu, Esra Ayhan; Tuzcu, Kasim; Basarslan, Fatmagul; Motor, Sedat; Coskun, Mesut; Keskin, Ugurcan; Ayintap, Emre; Ilhan, Ozgur; Oksuz, Huseyin
Abstract Objective: To examine the relationship of cataract forming effect of intravitreal triamcinolone acetonide (IVTA) injection with oxidative status and the effect of N-acetylcysteine (NAC) on these alterations. Materials and methods: Twenty-six Wistar-Albino rats were included in the study. Rats were assigned into four groups as follows: intravitreal saline injection group (controls); IVTA injection group; IVTA + intraperitoneal NAC injection group (IVTA + NAC); and intraperitoneal NAC injection group (NAC). Triamcinolone acetonide was intravitreally injected at a dose of 1 mg. NAC was intraperitoneally injected at a dose of 150 µg/g body weight. Animals were sacrificed and lens specimens were analyzed for levels of malondialdehyde (MDA) and protein carbonyl (PC) and activities of glutathione (GSH) and glutathione peroxidase (GSH-Px). Results: We found that the MDA and PC levels of lenses were increased in the IVTA group (p < 0.01). It was seen that GSH and GSH-Px in lenses were decreased in the IVTA group (p < 0.01). NAC administration significantly ameliorated these changes in the IVTA + NAC group (p < 0.05). Conclusion: These results indicate that the NAC produces a protective mechanism against IVTA-induced cataract and suggest a role of oxidative stress in pathogenesis.